Copper-based powder metallurgy friction material and preparation method thereof

By using an appropriate amount of tin sulfide and nickel-packed tungsten disulfide in copper-based powder metallurgical friction materials, the problems of unstable friction coefficient and abnormal wear amount at high speeds are solved, and friction stability and wear resistance are achieved The improvement meets the application needs of high-speed train carbon ceramic composite materials.

CN119491142AInactive Publication Date: 2025-02-21CENT SOUTH UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510081173.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-02-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When existing copper-based powder metallurgical friction materials are used at high speeds, the friction coefficient is unstable, the wear amount is abnormal and the damage is severe, making it difficult to meet the application needs of high-speed train carbon ceramic composite materials.

Method used

Using an appropriate amount and appropriate proportion of tin sulfide and nickel-clad tungsten disulfide, the friction stability and wear resistance of copper-based friction materials are improved through synergistic effects after sintering, and a friction braking requirement of 400km/h is prepared. Copper-based powder metallurgical friction material.

Benefits of technology

The friction stability of copper-based powder metallurgical friction materials has been improved and the wear amount has been greatly reduced, meeting the braking performance requirements under high-speed heavy-load equipment of 400km/h.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119491142A_ABST
    Figure CN119491142A_ABST
Patent Text Reader

Abstract

The invention relates to the field of design and preparation of powder metallurgy friction materials, in particular to a copper-based powder metallurgy friction material and a preparation method thereof. Raw materials used in the method comprise, by mass, 45%-55% of copper powder, 8%-20% of iron powder, 6%-15% of ferrochromium, 16%-22% of graphite, 0.5%-4% of molybdenum disulfide, 0.5%-4% of tin sulfide and 0.5%-4% of nickel-coated tungsten disulfide, and the mass ratio of the tin sulfide to the nickel-coated tungsten disulfide is (1-2): (1-2). In the nickel-coated tungsten disulfide, the content of nickel is 5-40%; the sum of the total amount of molybdenum disulfide, nickel-coated tungsten disulfide and tin sulfide is less than or equal to 5%. The preparation method comprises the following steps: weighing raw material powder according to the designed components, mixing, pressing and sintering to obtain the product. The composition design has the characteristics of scientificity, simple and controllable process and the like, and the obtained product has excellent tribological performance and completely meets the friction braking requirement of high-speed heavy-load equipment of 400km / h and above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of design and preparation of powder metallurgy friction materials, in particular to a copper-based powder metallurgy friction material and a preparation method thereof. Background Art

[0002] The higher operating speed of high-speed trains places higher performance requirements on friction materials. For example, cast steel brake discs are prone to thermal cracks, increased wear and other problems. Carbon-ceramic composites have excellent properties such as lightweight, high temperature resistance, and high wear resistance, and are expected to replace cast steel in the application of high-speed train brake disc materials. When the brake disc material is changed from cast steel to carbon-ceramic composites, the matching copper-based powder metallurgy friction material has performance problems such as unstable friction coefficient, abnormal wear and severe damage. Therefore, it is necessary to optimize the existing copper-based powder metallurgy friction material to meet the application of matching carbon-ceramic composites.

[0003] Copper-based powder metallurgy friction materials mainly include copper matrix, friction components (such as iron, ferrochrome, zirconium oxide, silicon oxide, silicon carbide, etc.) and lubricating components (molybdenum disulfide, graphite, etc.). In this material system, the friction components provide high friction coefficient and wear resistance, the lubricating components reduce the friction coefficient and lubricity, and the copper matrix carries the two components to achieve the synergy of friction and lubrication, so that the copper-based powder metallurgy friction material has both high and stable friction coefficient and wear resistance. Due to the large difference in surface uniformity of carbon-ceramic composite materials, there are more hard micro-convex bodies on the surface, and the thermal conductivity is low, which leads to greater damage to copper-based powder metallurgy friction materials.

[0004] The main solution to the above problems is alloying the matrix and ceramic modified particles. Patent CN112371972A uses copper-nickel alloy powder instead of electrolytic copper powder, which can meet the 350km / h braking standard conditions. However, the copper-nickel alloy powder strengthens the copper powder, resulting in insufficient sintering performance and reduced mechanical bonding performance of each component. Therefore, the braking performance at higher speeds is unknown.

[0005] Patents CN117904482A, CN11961912 A, and CN116287849A all report the use of composite ceramic components such as sepiolite, zirconium oxide-titanium nitride composite ceramic powders, etc. to introduce copper-based powder metallurgy friction materials. Importantly, the addition of ceramic components easily promotes the oxidation of the friction material surface to form a ceramic composite layer, which can easily lead to a low friction coefficient at high temperatures and insufficient braking performance. Therefore, the braking conditions mentioned in these patents are 24 m / s, 0.45 or 0.35 inertia, and a friction material area of ​​2240 mm. 2 Energy density is about 40 J / mm 2 , which only corresponds to 100km / h. This has limited reference significance for the development of copper-based friction materials that can meet the requirements of 400km / h with carbon ceramics.

[0006] As can be seen from the above, existing research and invention technologies are all focused on using complex alloy powders and ceramic composite powders to improve the friction coefficient and wear resistance of copper-based powder metallurgy friction materials, and due to the limitations of testing technology, the test conditions have not reached 400km / h. Since the copper matrix needs to form a good synergistic effect with metal, ceramic friction components and lubricating components, it is important that there is no report on the metal coating of the micro-lubricating component to achieve the performance improvement of copper-based powder metallurgy friction materials. Summary of the invention

[0007] The present invention attempts for the first time to develop a copper-based powder metallurgy friction material for high-speed train carbon-ceramic accessories by using trace components of tin sulfide and nickel-coated tungsten disulfide.

[0008] The present invention is based on Chinese patent CN201610962043.7, and optimizes and develops a copper-based powder metallurgy friction material with excellent performance and fully meeting the 400km / h friction braking requirements prepared by a simple process.

[0009] The present invention improves the friction stability and wear resistance of the copper-based friction material by sintering the product of tin sulfide and nickel-coated tungsten disulfide in an appropriate amount and proportion and high-temperature lubricity. The present invention obtains a copper-based powder metallurgy friction material that fully meets the 400km / h friction braking requirements by combining the action of tin sulfide and tungsten disulfide in an appropriate amount and proportion with other appropriate components.

[0010] The invention discloses a copper-based powder metallurgy friction material. The raw material components used in the material are composed of the following components by mass percentage: 45-55% of copper powder, 8-20% of iron powder, 6-15% of ferrochrome, 16-22% of graphite, 0.5-4% of molybdenum disulfide, 0.5-4% of tin sulfide and 0.5-4% of nickel-coated tungsten disulfide, and the mass ratio of tin sulfide to nickel-coated tungsten disulfide is 1-2:1-2; the content of nickel in the nickel-coated tungsten disulfide is 5-40%; and the total amount of molybdenum disulfide, nickel-coated tungsten disulfide and tin sulfide is less than or equal to 5%.

[0011] The invention discloses a copper-based powder metallurgy friction material, which contains tin sulfide and tungsten disulfide in appropriate amounts and proportions and is obtained by combining other components, and can better adapt to the carbon-ceramic composite material to ensure reliability under high-speed and high-temperature braking.

[0012] Preferably, the tin sulfide particle size range is less than 100 mesh.

[0013] Preferably, the nickel-coated tungsten disulfide has a particle size range of less than 100 mesh.

[0014] Preferably, the present invention provides a copper-based powder metallurgy friction material for high-speed train carbon-ceramic accessories and a preparation method thereof, wherein the purity of tin sulfide is >99.5%, and the purity of nickel-coated tungsten disulfide is >99.7%.

[0015] Among the raw materials used, the total amount of sulfides (molybdenum disulfide, nickel-coated tungsten disulfide, and tin sulfide) is no more than 5%. This is because the sintering diffusion and reaction of sulfides and the copper matrix need to be controlled. If too much is used, the presence of excessive sulfides will accelerate the reaction between copper and sulfides in the sintering process, reducing the copper content and material uniformity.

[0016] Further preferably, the copper-based powder metallurgy friction material of the present invention comprises the following raw material components, measured in mass percentage: 50-54% copper powder, 16-19% iron powder, 7-10%, 16-20% ferrochrome powder, 1-1.5% molybdenum disulfide, 0.5-1.5% tin sulfide, and 0.5-1.5% nickel-coated tungsten disulfide.

[0017] Further preferred, the copper-based powder metallurgy friction material of the present invention comprises the following raw material components by mass percentage: 53% copper powder, 18% iron powder, 8% ferrochrome powder, 19% graphite, 1% molybdenum disulfide, 1% tin sulfide, and 1% nickel-coated tungsten disulfide. The friction curve stability of the obtained copper-based powder metallurgy friction material is improved, and the wear amount is greatly reduced. Especially when used on high-speed and heavy-load equipment at 400Km / h, its performance is more superior.

[0018] In the present invention, the particle size of the copper powder is 200-300 meshes.

[0019] In the present invention, the particle size of the iron powder is 200-300 meshes.

[0020] In the present invention, the particle size of the ferrochrome powder is less than 200 meshes.

[0021] In the present invention, the particle size of graphite is 10-100 meshes.

[0022] In the present invention, the particle size of nickel-coated molybdenum disulfide is 100-200 meshes.

[0023] In the present invention, the ferrochrome is preferably low carbon ferrochrome.

[0024] As a further preference, in the low carbon ferrochrome, Cr ≥ 52wt%, C ≤ 0.06wt%, and Fe as the balance.

[0025] Preferably, the nickel content in the nickel-coated tungsten disulfide is 5-10%.

[0026] The present invention provides a method for preparing a copper-based powder metallurgy friction material, comprising the following steps:

[0027] (1) Raw material mixing: Copper powder, iron powder, ferrochrome powder and graphite powder are mixed according to the designed composition; molybdenum disulfide, nickel-coated tungsten disulfide and tin sulfide are mixed according to the designed composition; the two mixed powders are mixed again and then kerosene (3% to 5% of the total mass of the prepared powder) is added, and mixed by a roller to obtain a uniform powder.

[0028] (2) Compression molding: Add the evenly mixed powder in (1) into a mold and obtain a molded blank by cold pressing.

[0029] (3) Pressure sintering: The formed blank obtained in (2) is placed in a pressure sintering furnace under a protective atmosphere at a sintering temperature of 900-950°C, a pressure of 1.5-2 MPa, and a holding time of 2-3 hours. The blank is then cooled in the furnace to obtain a copper-based powder metallurgy friction material.

[0030] The particle size range of tin sulfide is less than 100 mesh, and the particle size range of nickel-coated tungsten disulfide is less than 100 mesh. The particle size of both powders is smaller than that of molybdenum disulfide. The dispersion of two fine particles inside the coarse particles can be achieved through the mixing process to ensure the uniformity of the distribution of sulfides. Too large a particle size will lead to insufficient reaction with the copper matrix, and too small a particle size will lead to excessive reaction, which will not guarantee both the reaction product and the original structure of the original tungsten disulfide, tin sulfide and molybdenum disulfide. It can improve the interface bonding between the copper matrix and the sulfide and the high-temperature lubrication effect of the sulfide itself. The introduction of tin enables the copper matrix to achieve solid solution strengthening, and the introduction of tungsten improves the high-temperature wear resistance of the copper matrix.

[0031] As a preferred embodiment, the nickel-coated tungsten disulfide in the present invention is prepared by the following steps:

[0032] Disperse tungsten disulfide powder in deionized water at a concentration of 5-35 g / L and stir to obtain a uniform suspension. Add a nickel nitrate solution with a concentration of 0.01-0.05 mol / L in a volume ratio of 1:(0.9-1.0) to the suspension, and dropwise add a reducing agent (sodium borohydride solution) with a volume ratio of 1:(2-2.5) to the suspension to perform reduction deposition of nickel ions under stirring. To ensure the reaction efficiency and deposition uniformity, adjust the system pH to 8-9 and react at a temperature of 40-70°C for 1-2 hours. After the reaction is completed, wash with deionized water several times to remove residual impurities, and then dry in a vacuum or inert atmosphere to obtain nickel-coated tungsten disulfide powder.

[0033] In the present invention, the amount of the reducing agent used is 1.0 times or more of the theoretical amount for completely reducing the nickel in the nickel salt.

[0034] The present invention designs and prepares a copper-based powder metallurgy friction material for high-speed train carbon-ceramic accessories and a preparation method thereof. In step (2), the cold pressing pressure is 25-30 MPa and the holding time is 2-5 s.

[0035] The copper-based powder metallurgy friction material for high-speed train carbon-ceramic accessories and its preparation method are designed and prepared by the present invention. The open porosity of the obtained product is less than 8%, and the density is greater than 4.8 g / cm 3 , Brinell hardness> 17HB.

[0036] The present invention designs and prepares a copper-based powder metallurgy friction material for high-speed train carbon-ceramic matching and a preparation method thereof. Under the working condition simulating the emergency braking condition of 400 km / h, the friction coefficient of the obtained product is between 0.35 and 0.40, the friction stability coefficient is greater than 0.8, and the wear loss is 0.05 to 0.10 cm 3 / MJ. Under the working condition simulating the emergency braking condition of 200km / h, the friction coefficient of the obtained product is between 0.35~0.40, the friction stability coefficient is greater than 0.8, and the wear volume is 0.01~0.02cm 3 The product obtained by the present invention has a higher friction stability coefficient and a significantly reduced wear amount, meeting the standard requirements.

[0037] The present invention uses nickel-coated tungsten disulfide and tin sulfide in an appropriate amount and proportion, which can, on the one hand, improve the strength of the copper-based powder metallurgy friction material matrix, cleverly introduce metal element strengthening materials, and improve the friction coefficient and wear resistance; on the other hand, the high-temperature lubrication performance of tungsten disulfide and tin sulfide can be used to significantly improve the friction stability; the preparation process of the present invention is simple and efficient, the overall strength of the copper-based powder metallurgy friction material is improved, and the friction stability coefficient and wear resistance are improved.

[0038] Beneficial Effects

[0039] The present invention uses an appropriate amount and proportion of nickel-coated tungsten disulfide and tin sulfide to improve the strength of the copper-based powder metallurgy friction material matrix, cleverly introduce metal element reinforcement materials, and improve the friction coefficient and wear resistance; on the other hand, the high-temperature lubrication performance of tungsten disulfide and tin sulfide can be used to significantly improve the friction stability; the preparation process of the present invention is simple and efficient, the overall strength of the copper-based powder metallurgy friction material is improved, and the friction stability coefficient and wear resistance are improved. Compared with the existing copper-based powder metallurgy friction material that has not been reinforced by multiple sulfides, it shows better adaptability.

[0040] The high wear-resistant copper-based powder metallurgy friction material provided by the present invention has less surface damage and minimal damage to the mating parts during braking, has a high friction coefficient, stable braking performance, and excellent wear resistance, and does not require additional pretreatment of the powder, has a simple and efficient preparation process, and does not use environmentally unfriendly raw materials.

[0041] The highly wear-resistant copper-based powder metallurgy friction material designed and prepared by the present invention exhibits excellent performance under simulated 400km / h emergency braking conditions, and is particularly far superior to the products obtained by the prior art. When the product obtained by combining an appropriate amount and proportion of nickel-coated tungsten disulfide and tin sulfide with other components is applied to 400km / h emergency braking, the reaction between the copper matrix and nickel and tin during the sintering process strengthens the matrix and component interface, realizes the in-situ pinning effect, and improves wear resistance; on the other hand, it protects the reaction loss of tungsten disulfide and ensures high-temperature lubricity. If non-coated tungsten disulfide powder is used, it is easy to cause copper and tungsten disulfide to react violently and precipitate tungsten, reduce the quality of tungsten disulfide, and introduce too much hard phase, which is easy to cause fatigue wear and damage. If the ratio is unbalanced, it will lead to deviations in sintering reaction and diffusion, reduce material uniformity, and reduce comprehensive performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is a physical picture of the product obtained in Example 1.

[0043] Figure 2 The braking curve is obtained by simulating a 400 km / h braking test on a Shuntong MM3000 high-speed friction and wear testing machine for the product obtained in Example 1.

[0044] Figure 3 The braking curve of the product obtained in Example 2 was obtained by simulating a 400 km / h braking test on a Shuntong MM3000 high-speed friction and wear testing machine.

[0045] Figure 4 The braking curve of the product obtained in comparative example 1 was obtained by simulating a 400 km / h braking test on a Shuntong MM3000 high-speed friction and wear testing machine. DETAILED DESCRIPTION

[0046] The embodiment of the present invention provides a copper-based powder metallurgy friction material for high-speed train carbon-ceramic matching and a preparation method thereof. By matching with carbon-ceramic, the 400km / h emergency braking condition is simulated to show excellent braking performance.

[0047] The test machine used in the present invention to simulate 400 km / h braking is a Shuntong MM3000 high-speed friction and wear test machine (manufactured by Xi'an Shuntong Electromechanical Application Technology Research Institute), with an actual speed of 6400 rpm and an inertia of 1.035 kg×m 2 ; Friction area is 3.7mm 2 , the energy density acting on the friction material is 617.28J / mm 2, which is consistent with the calculation results of braking parameters in the actual national standard. The parameters for simulating 200km / h braking are consistent with those for simulating 400km / h braking, except that the actual speed is 3200 rpm.

[0048] The performance of the embodiments of the present invention and the comparative examples are shown in Table 1 and Table 2.

[0049] Example 1

[0050] (1) Preparation of nickel-coated tungsten disulfide: Disperse 45.8g of tungsten disulfide powder in 1.5L of deionized water and stir to obtain a uniform suspension. Add 1.43L of 0.05mol / L nickel nitrate solution, and drop 3.58L of 0.02mol / L reducing agent (sodium borohydride solution) to perform reduction deposition of nickel ions under stirring. To ensure reaction efficiency and deposition uniformity, adjust the system pH to 8 and react at 55°C for 90min. After the reaction is completed, wash with deionized water several times to remove residual impurities, and then dry in an inert atmosphere to obtain 48.9g of nickel-coated tungsten disulfide powder.

[0051] (2) Raw material mixing: according to the designed composition (mass percentage), 53% copper powder (particle size: 150-300 mesh), 18% iron powder (particle size: 200-300 mesh), 8% ferrochrome powder (particle size: ~200 mesh), 19% graphite (particle size: 50-100 mesh) were manually mixed; 1% molybdenum disulfide (particle size: 100-200 mesh), 1% tin sulfide (particle size: less than 100 mesh), 1% nickel-coated tungsten disulfide (particle size: less than 100 mesh); then 5% kerosene of the total mass of the prepared powder was added and mixed by roller to obtain a uniform powder.

[0052] (3) Pressing: Add the evenly mixed powder in (2) into the mold and cold press to obtain a blank with an outer diameter of 75 mm and an inner diameter of 53 mm. The cold press pressure is 29 MPa and the holding time is 3 s.

[0053] (4) Pressure sintering: The formed blank obtained in (3) was placed in a pressure sintering furnace under H2 protective atmosphere, with a sintering temperature of 950°C, a pressure of 2 MPa, and a holding time of 2.5 hours. The copper-based powder metallurgy friction material was then cooled in the furnace and the friction area was processed to 3.7 mm. 2 .

[0054] (5) Test results: The high wear-resistant copper-based powder metallurgy friction material obtained in this embodiment has an open porosity of 7.0% and a density of 4.95 g / cm 3 , Brinell hardness is 18 HB.

[0055] The high wear-resistant copper-based powder metallurgy friction material designed and prepared by the present invention has a friction coefficient of 0.38, a friction stability coefficient of 0.90, and a wear loss of 0.05 cm under the working condition of simulating the emergency braking condition of 400 km / h. 3 / MJ; under the working condition simulating the emergency braking condition of 200km / h, the friction coefficient is 0.36, the friction stability coefficient is 0.93, and the wear volume is 0.011 cm 3 / MJ.

[0056] Example 2

[0057] The conditions are the same as those in Example 1, except that: 0.7% tin sulfide (particle size: less than 100 mesh) and 1.3% nickel-coated tungsten disulfide (particle size: less than 100 mesh).

[0058] Test results: The high wear-resistant copper-based powder metallurgy friction material obtained in this embodiment has an open porosity of 7.3% and a density of 4.91 g / cm 3 , Brinell hardness is 19 HB.

[0059] The high wear-resistant copper-based powder metallurgy friction material designed and prepared by the present invention has a friction coefficient of 0.37, a friction stability coefficient of 0.92, and a wear loss of 0.06 cm under the working condition of simulating the emergency braking condition of 400 km / h. 3 / MJ; under the working condition simulating the emergency braking condition of 200km / h, the friction coefficient is 0.36, the friction stability coefficient is 0.93, and the wear volume is 0.013 cm 3 / MJ.

[0060] It can be seen from Examples 1 and 2 that in the present invention, by controlling the type and content of sulfide, the copper-based powder metallurgy friction material can have a high friction coefficient and high stability when paired with a carbon-ceramic composite material.

[0061] Example 3

[0062] The conditions are the same as those in Example 1, except that: 1.3% tin sulfide (particle size: less than 100 mesh) and 0.7% nickel-coated tungsten disulfide (particle size: less than 100 mesh).

[0063] Test results: The high wear-resistant copper-based powder metallurgy friction material obtained in this embodiment has an open porosity of 6.5% and a density of 4.97 g / cm 3 , Brinell hardness is 21 HB.

[0064] The high wear-resistant copper-based powder metallurgy friction material designed and prepared by the present invention has a friction coefficient of 0.35, a friction stability coefficient of 0.85, and a wear loss of 0.06 cm under the working condition of simulating the emergency braking condition of 400 km / h. 3 / MJ; under the condition of simulating emergency braking at 200km / h, the friction coefficient is 0.36, the friction stability coefficient is 0.88, and the wear volume is 0.015 cm 3 / MJ.

[0065] Example 4

[0066] The conditions are the same as those in Example 1, except that: 0.85% tin sulfide (particle size: less than 100 mesh) and 1.15% nickel-coated tungsten disulfide (particle size: less than 100 mesh).

[0067] Test results: The high wear-resistant copper-based powder metallurgy friction material obtained in this embodiment has an open porosity of 7.0% and a density of 4.95 g / cm 3 , Brinell hardness is 20 HB.

[0068] The high wear-resistant copper-based powder metallurgy friction material designed and prepared by the present invention has a friction coefficient of 0.36, a friction stability coefficient of 0.88, and a wear loss of 0.08 cm under the working condition of simulating the emergency braking condition of 400 km / h. 3 / MJ. Under the condition of simulating emergency braking at 200km / h, the friction coefficient is 0.37, the friction stability coefficient is 0.88, and the wear volume is 0.014 cm 3 / MJ.

[0069] Example 5

[0070] The conditions are the same as those in Example 1, except that: 1.15% tin sulfide (particle size: less than 100 mesh) and 0.85% nickel-coated tungsten disulfide (particle size: less than 100 mesh).

[0071] Test results: The high wear-resistant copper-based powder metallurgy friction material obtained in this embodiment has an open porosity of 7.3% and a density of 5.00 g / cm 3 , Brinell hardness is 22 HB.

[0072] The high wear-resistant copper-based powder metallurgy friction material designed and prepared by the present invention has a friction coefficient of 0.37, a friction stability coefficient of 0.91, and a wear loss of 0.07 cm under the working condition of simulating the emergency braking condition of 400 km / h. 3 / MJ; under the working condition simulating the emergency braking condition of 200km / h, the friction coefficient is 0.35, the friction stability coefficient is 0.91, and the wear volume is 0.017 cm 3 / MJ.

[0073] Comparative Example 1

[0074] Other conditions are the same as those in Example 1, except that: 1% tin sulfide (particle size: less than 100 mesh) and 1% non-coated tungsten disulfide (particle size: less than 100 mesh).

[0075] Test results: The high wear-resistant copper-based powder metallurgy friction material obtained in this comparative example has an open porosity of 9.0% and a density of 4.84 g / cm 3 , Brinell hardness is 25 HB.

[0076] The high wear-resistant copper-based powder metallurgy friction material obtained in this comparative example has a friction coefficient of 0.28, a friction stability coefficient of 0.77, and a wear loss of 0.17 cm under the working condition of simulating the emergency braking condition of 400 km / h. 3 / MJ; under the working condition simulating the emergency braking condition of 200km / h, the friction coefficient is 0.24, the friction stability coefficient is 0.78, and the wear volume is 0.03 cm 3 / MJ.

[0077] Subsequent research found that: the lack of coated tungsten disulfide resulted in excessive reaction between tungsten disulfide and copper matrix to generate tungsten and copper sulfide, and the hardness of the material increased, resulting in a small initial contact area and small adhesive wear due to high hardness. Therefore, due to the accumulation of friction heat, the friction coefficient increased in the later stage of braking, resulting in reduced braking stability. Therefore, it can be seen that the role of nickel-coated tungsten disulfide is very significant.

[0078] Comparative Example 2

[0079] Other conditions are the same as those in Example 1, except that tin sulfide is 0% (particle size is less than 100 mesh) and nickel-coated tungsten disulfide is 2% (particle size is less than 100 mesh).

[0080] Test results: The high wear-resistant copper-based powder metallurgy friction material obtained in this comparative example has an open porosity of 8.4% and a density of 4.91 g / cm 3 , Brinell hardness is 25 HB.

[0081] The high wear-resistant copper-based powder metallurgy friction material obtained in this comparative example has a friction coefficient of 0.28, a friction stability coefficient of 0.72, and a wear loss of 0.22 cm under the working condition of simulating the emergency braking condition of 400 km / h. 3 / MJ; under the working condition simulating the emergency braking condition of 200km / h, the friction coefficient is 0.26, the friction stability coefficient is 0.73, and the wear volume is 0.025 cm 3 / MJ.

[0082] Comparative Example 3

[0083] Other conditions are the same as those in Example 1, except that tin sulfide is 2% (particle size: less than 100 mesh) and nickel-coated tungsten disulfide is 0% (particle size: less than 100 mesh).

[0084] Test results: The high wear-resistant copper-based powder metallurgy friction material obtained in this comparative example has an open porosity of 7.7% and a density of 4.96 g / cm 3 , Brinell hardness is 21 HB.

[0085] The high wear-resistant copper-based powder metallurgy friction material obtained in this comparative example has a friction coefficient of 0.31, a friction stability coefficient of 0.84, and a wear loss of 0.13 cm under the working condition of simulating the emergency braking condition of 400 km / h. 3 / MJ; under the condition of simulating emergency braking at 200km / h, the friction coefficient is 0.31, the friction stability coefficient is 0.68, and the wear volume is 0.022 cm 3 / MJ.

[0086] Comparative Example 4

[0087] Other conditions are the same as those in Example 1, except that copper powder is 51% (particle size: 150-300 mesh), tin sulfide is 2% (particle size: 100-150 mesh), and nickel-coated tungsten disulfide is 2% (particle size: 100-200 mesh).

[0088] The friction material in this comparative example has an open porosity of 7.9% and a density of 4.83 g / cm 3 , Brinell hardness is 19 HB.

[0089] The friction material in this comparative example has a friction coefficient of 0.24, a friction stability coefficient of 0.93, and a wear loss of 0.08 cm under the working condition of simulating the emergency braking condition of 400 km / h. 3 / MJ; under the condition of simulating emergency braking at 200km / h, the friction coefficient is 0.21, the friction stability coefficient is 0.91, and the wear volume is 0.014 cm 3 / MJ.

[0090] .

[0091] .

[0092] The embodiments and comparative examples of the present invention are only provided to further illustrate the present invention in detail.

Claims

1. A copper-based powder metallurgy friction material, characterized in that: The raw material components used are composed of the following components in percentage by mass: 45-55% copper powder, 8-20% iron powder, 6-15% ferrochrome, 16-22% graphite, 0.5-4% molybdenum disulfide, 0.5-4% tin sulfide, 0.5-4% nickel-coated tungsten disulfide, and the mass ratio of tin sulfide to nickel-coated tungsten disulfide is 1-2:1-2; the nickel content in nickel-coated tungsten disulfide is 5-40%; the total amount of molybdenum disulfide, nickel-coated tungsten disulfide and tin sulfide is less than or equal to 5%; The nickel-coated tungsten disulfide is prepared by the following steps: The tungsten disulfide powder is dispersed in deionized water at a concentration of 5-35 g / L, and stirred to obtain a uniform suspension; nickel nitrate with a concentration of 0.01-0.05 mol / L is added as a nickel salt solution, and 0.01-0.05 mol / L of a reducing agent is added dropwise to perform reduction deposition of nickel ions under stirring conditions; during reduction, the pH value of the system is controlled at 8-9, the reaction temperature is controlled at 40°C-70°C, and the reaction time is controlled at 1-2h; after the reaction is completed, it is washed with deionized water and then dried in a vacuum or inert atmosphere to obtain nickel-coated tungsten disulfide powder.

2. The copper-based powder metallurgy friction material according to claim 1, characterized in that: The particle size range of tin sulfide is less than 100 mesh; the particle size range of nickel-coated tungsten disulfide is less than 100 mesh.

3. The copper-based powder metallurgy friction material according to claim 1, characterized in that: The purity of tin sulfide is >99.5%, and the purity of nickel-coated tungsten disulfide is >99.7%.

4. The copper-based powder metallurgy friction material according to claim 1, characterized in that: The raw material components used are calculated by mass percentage and consist of the following components: 50-54% copper powder, 16-19% iron powder, 7-10% ferrochrome powder, 16-20% ferrochrome powder, 1-1.5% molybdenum disulfide, 0.5-1.5% tin sulfide, and 0.5-1.5% nickel-coated tungsten disulfide.

5. The copper-based powder metallurgy friction material according to claim 1, characterized in that: The raw material components used are composed of the following components in percentage by mass: 53% copper powder, 18% iron powder, 8% ferrochrome powder, 19% graphite, 1% molybdenum disulfide, 1% tin sulfide, and 1% nickel-coated tungsten disulfide.

6. The copper-based powder metallurgy friction material according to claim 1, characterized in that: The particle size of copper powder is 200~300 mesh; the particle size of iron powder is 200~300 mesh; the particle size of ferrochrome powder is less than 200 mesh; the particle size of graphite is 10~100 mesh; the particle size of molybdenum disulfide is: 100~200 mesh.

7. A method for preparing a copper-based powder metallurgy friction material according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Raw material mixing: Copper powder, iron powder, ferrochrome powder and graphite powder are mixed according to the designed composition; molybdenum disulfide, nickel-coated tungsten disulfide and tin sulfide are mixed according to the designed composition; the two mixed powders are mixed again and then kerosene of 3-5% of the total mass of the prepared powder is added, and mixed by a roller to obtain a uniform powder; (2) Pressing: Add the powder mixed evenly in (1) into a mold and cold press to obtain a formed blank; (3) Pressure sintering: The formed blank obtained in (2) is placed in a pressure sintering furnace under a protective atmosphere at a sintering temperature of 900-950°C, a pressure of 1.5-2 MPa, and a holding time of 2-3 hours. The blank is then cooled in the furnace to obtain a copper-based powder metallurgy friction material.

8. The method for preparing a copper-based powder metallurgy friction material according to claim 7, characterized in that: In step (2), the cold pressing pressure is 25-30 MPa and the holding time is 2-5 s.

9. The method for preparing a copper-based powder metallurgy friction material according to claim 7, characterized in that: Under the working condition simulating the emergency braking condition of 400km / h, the friction coefficient of the obtained copper-based powder metallurgy friction material is between 0.35 and 0.40, the friction stability coefficient is greater than 0.8, and the wear loss is 0.05-0.10 cm 3 / MJ; under the working condition simulating the emergency braking condition of 200km / h, the friction coefficient of the obtained copper-based powder metallurgy friction material is between 0.35 and 0.40, the friction stability coefficient is greater than 0.8, and the wear loss is 0.01~0.02 cm 3 / Between MJ.

Citation Information

Patent Citations

  • Super-simple component powder metallurgy friction material for high-speed train brake pad

    CN106399743A

  • Powder metallurgy brake pad lining friction body for carbon-ceramic brake disc of motor train unit and preparation method thereof

    CN112371972A

  • Copper-based friction material paired with carbon ceramic plate and preparation method of copper-based friction material

    CN116287849A